ANALISIS FAKTOR PENYEBAB LUNTURNYA TRADISI MARTAROMBO DI KALANGAN MAHASISWA SUKU BATAK TOBA DI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JAMBI - Pasmaida Manalu, Maria; Dewi, Nurmalia; Wela Sasih, Agustin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The martarombo tradition is an important cultural practice in the Toba Batak community, serving to establish kinship ties through clans. However, among the younger generation, particularly university students, this tradition is becoming less common, raising concerns that it could diminish understanding of the kinship system within Toba Batak culture. This study aims to identify the factors contributing to the decline of the martarombo tradition among Toba Batak students at the Faculty of Teacher Training and Education, Jambi University, and its impacts, as well as efforts to preserve it. This study employed a qualitative approach with descriptive methods. Data collection techniques included interviews, observation, and documentation with Toba Batak students as informants. The results indicate that the decline of the martarombo tradition is influenced by a lack of cultural understanding, the influence of technological developments, interaction with other cultures, and student life abroad. These conditions have resulted in a decline in knowledge regarding the customs and kinship relationships within Toba Batak society. Based on the research results, it can be concluded that preserving the Martarombo tradition requires the involvement of families, the social environment, and the awareness of the younger generation to ensure the preservation of Toba Batak cultural values ​​amidst changing times. These efforts can be achieved through cultural education within families and campuses, as well as the use of social media for educational purposes.